Mobilidade de pregas vocais e sensibilidade laríngea em pacientes disfágicos pós-AVE - Fiorese, Ana Carolina [UNIFESP] (2010)
Objectives: To investigate the interference of vocal folds mobility and larynx sensitivity alterations in deglutition dynamics on patients after encephalic vascular accident (EVA), admitted on oropharyngeal dysphagia ambulatory, evaluated by nasolaryngoscopy. Materials and Methods: A retrospective charts review of adult patients after EVA that were submitted to objective deglutition evaluation using nasolaryngoscopy. Data on personal background, time of the cerebral lesion and results of the instrumental deglutition assessment was contrasted with the vocal folds mobility alterations and laryngeal sensitivity, observed during the nasolaryngoscopy. Results: The sample was constituted of 55 dysphagic patients (36 male and 19 female) with ages ranging between 30 and 84 years (mean age of 63.7 years). Time of the lesion varied from 7 days to 10 years (120 months), mean of 14 months. When correlating the presence of vocal folds mobility alterations and laryngeal sensitivity with laryngeal penetration, tracheal aspiration and pharyngeal recesses residue, respectively, there were no statistically significant correlations in any of the associations. Conclusions: There was no association between vocal folds mobility loss and laryngeal sensitivity and laryngeal penetration, tracheal aspiration and food residue in the pharyngeal recesses.